2017
DOI: 10.1039/c7an01084b
|View full text |Cite
|
Sign up to set email alerts
|

Highly active 3-dimensional cobalt oxide nanostructures on the flexible carbon substrates for enzymeless glucose sensing

Abstract: The demand for electrochemical sensors with high sensitivity and reliability, fast response, and excellent selectivity has stimulated intensive research on developing highly active nanomaterials. In this work, freestanding 3D/Co 3 O 4 thorn-like and wire-like (nanowires) nanostructures are directly grown on a flexible carbon fiber paper (CFP) substrate by a single-step hydrothermal process without using surfactants or templates. The 3D/Co 3 O 4 thorn-like nanostructures show higher electrochemical activity tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…The tiny redox peaks located at approximately 0.28 V and 0.23 V may be assigned to the redox process of Co(II)/Co(III), while the larger ones at 0.53 V and 0.52 V to the redox process of Co(III)/Co(IV). From the picture, one can tell that the former redox couple shows scarcely catalytic activity towards glucose oxidation whereas the latter one does . By comparison, it seems that the black plot (without glucose) of the NiCo 2 O 4 /GCE exhibits only a couple of peaks sited at 0.45 V and 0.37 V (Figure d), of which the mechanism is considered to be a little more complicated than pure Co 3 O 4 or NiO alone in that two metal species with different valent states in NiCo 2 O 4 are involved in the redox process simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…The tiny redox peaks located at approximately 0.28 V and 0.23 V may be assigned to the redox process of Co(II)/Co(III), while the larger ones at 0.53 V and 0.52 V to the redox process of Co(III)/Co(IV). From the picture, one can tell that the former redox couple shows scarcely catalytic activity towards glucose oxidation whereas the latter one does . By comparison, it seems that the black plot (without glucose) of the NiCo 2 O 4 /GCE exhibits only a couple of peaks sited at 0.45 V and 0.37 V (Figure d), of which the mechanism is considered to be a little more complicated than pure Co 3 O 4 or NiO alone in that two metal species with different valent states in NiCo 2 O 4 are involved in the redox process simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Table S1 briefly summarizes the effect of parameters on the sensing properties of hydrothermally synthesized CoO and their composites. Kannan et al reported thorn- and nanowire-like morphologies of Co 3 O 4 after reversing the molar ratio of the precursor used as shown in Figure (i). The thorn-like morphology with a length of 3–4 μm has a greater surface area (86.2 m 2 g –1 ) than the nanowire (67.5 m 2 g –1 ) and a sensitivity of 180 μA mM –1 cm –2 .…”
Section: Metal Oxide-based Nonenzymatic Glucose Sensormentioning
confidence: 99%
“…(ii) (a) Current response by CFP electrode for dropwise addition of 1 μM glucose with respect to time, (b) calibration curve for known amount of glucose concentration, (c) current response of CFP electrode to glucose concentration up to 1000 μM with inset showing corresponding calibration curve, (d) current response of CFP electrode toward addition of different interfering compounds having concentrations of 100 μM. Reprinted with permission from ref . Copyright 2017, Royal Society of Chemistry.…”
Section: Metal Oxide-based Nonenzymatic Glucose Sensormentioning
confidence: 99%
“…As a member of glucose sensors, non-enzymatic glucose sensors based on the direct electrocatalysis of glucose have recently drawn great attention due to their efficient glucose detection sensitivity and stability [ 2 , 5 , 6 , 7 ]. Owing to the high electrocatalytic ability, materials based on noble metals, such as Pt [ 8 ], Pd [ 9 ], and Ag [ 10 ], transition metals, such as Cu [ 11 ], Ni [ 12 , 13 ], Mn [ 14 ], and Co [ 15 ], and their oxides [ 16 ], or polymers, such as polyaniline [ 17 ], have been found to be active electrocatalytic materials for glucose biosensors. Among them, cuprous oxide (Cu 2 O), an important semiconductor with a band gap of 2.2 eV [ 18 ], has exhibited promising applications in the field of sensing, which is attributed to its minimal cost, stability, and significant catalytic activity [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%